Microvascular Permeability and Texture Analysis of the Skeletal Muscle of Diabetic Rabbits With Critical Limb Ischaemia Based on DCE-MRI - Yang, Qi; Li, Liang; Zha, Yunfei; Yan, Yuchen; Xing, Dong; Liu, Huan; Yang, Liu; Peng, Lin; Zhang, Yubiao (Frontiers in Endocrinology, 2022)
Background: We evaluated skeletal muscle vascular permeability in diabetic rabbits with critical limb ischaemia using quantitative dynamic contrast agent-enhanced (DCE) magnetic resonance imaging (MRI) and explored the feasibility of using DCE-MRI Ktrans-based texture analysis for assessing early slight ischaemia-related skeletal muscle structural changes. Method: Twenty-four male New Zealand white rabbits (2.7 ± 0.3 kg; n = 12 each in sham-operated and experimental groups) underwent axial MRI of the vastus lateralis muscle at 1, 2, and 3 weeks after alloxan injection. Between-group and intra-group postoperative permeability and texture parameters were compared. Texture features of experimental groups in the third week were modelled by receiver operating characteristic (ROC) curve analysis. Correlations of permeability and of statistical texture parameters with peripheral blood endothelial progenitor cells (EPCs) and microvascular density (MVD) were analysed. Results: In the experimental group, the transfer constant (Ktrans) was statistically significant at all time-points (F = 5.800, P = 0.009). Their vastus lateralis muscle Ktrans was significantly lower in the third than in the first week (P = 0.018) and correlated positively with peripheral blood EPCs in the experimental group (r = 0.598, [95% CI: 0.256, 0.807]). The rate constant was negatively associated with vastus lateralis muscle MVD (r = -0.410, [95% CI: -0.698, -0.008]). The area under the ROC curve of texture parameters based on Ktrans in ischaemic limbs was 0.882. Conclusions: Quantitative DCE-MRI parameters could evaluate microvascular permeability of ischaemic limb skeletal muscle, and texture analysis based on DCE-MRI Ktrans allowed evaluation of early slight skeletal muscle structural changes.